Transparency and Accountability in Corporate Social Responsibility Programs: Local Government Oversight through a Business Law Perspective - Setiawati, Diana; Soepatini; Hanifah Febriani; Chintya Anggraeni (Law and Justice, 2024)
Corporate Social Responsibility (CSR) is increasingly recognized as more than just a corporate obligation—it is a strategic approach to achieving sustainable development goals. In Indonesia, where regional autonomy gives local governments significant authority, their role in supervising CSR becomes particularly important, especially in ensuring transparency and accountability. Despite this, many CSR programs still suffer from a lack of clear oversight, limited regulatory support, and varying levels of corporate commitment. This study explores how local governments carry out their supervisory role in CSR programs from the perspective of business law. Using a qualitative juridical-normative approach complemented by field data, this research focuses on Klaten, Central Java, as a case study. Data were obtained through interviews with local officials, CSR practitioners, and community members, as well as analysis of regional regulations and corporate CSR reports. The findings reveal that while some local governments have made efforts to regulate CSR through regional policies, the lack of binding legal instruments and standardized monitoring systems poses significant challenges. In many cases, accountability still depends more on voluntary compliance than enforceable obligations. Moreover, transparency in CSR reporting is often limited, making it difficult for stakeholders to evaluate the actual impact. The study concludes that strengthening the legal basis of CSR at the local level—through clearer regulations, transparent reporting standards, and inclusive supervision involving civil society—could lead to more effective CSR governance. This would not only improve corporate accountability but also ensure that CSR efforts align more closely with community needs and sustainable development goals. Keywords: CSR, business law, local government, accountability